2021
DOI: 10.1002/ccd.29584
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of percutaneous debulking of tricuspid valve endocarditis in intravenous drug users

Abstract: Objectives A retrospective case series of a percutaneous approach to debulk tricuspid valve endocarditis (TVE) using an 8 French mechanical aspiration system in patients with a history of intravenous drug use (IVDU) was reported. IVDU associated TVE is increasing in the United States and is associated with high mortality despite early surgical debridement. Patients with advanced disease, shock, and respiratory failure may not be candidates for surgical debridement or replacement. These patients have recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Our study revealed an upward trend in PMA use in the management of RSIE which has been reflected in the literature, as there has been an increase in case series and registry data showing the expansion of the motives and applications of PMA in RSIE 12–17 . PMA has been predominately used in cases of RSIE as an adjunct to management where a response to appropriate antimicrobial therapy is not achieved or immediate valve surgery is not feasible.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our study revealed an upward trend in PMA use in the management of RSIE which has been reflected in the literature, as there has been an increase in case series and registry data showing the expansion of the motives and applications of PMA in RSIE 12–17 . PMA has been predominately used in cases of RSIE as an adjunct to management where a response to appropriate antimicrobial therapy is not achieved or immediate valve surgery is not feasible.…”
Section: Discussionmentioning
confidence: 57%
“…Our study revealed an upward trend in PMA use in the management of RSIE which has been reflected in the literature, as there has been an increase in case series and registry data showing the expansion of the motives and applications of PMA in RSIE. [12][13][14][15][16][17] PMA has been predominately used in cases of RSIE as an adjunct to management where a response to appropriate antimicrobial therapy is not achieved or immediate valve surgery is not feasible. The indications for PMA have included: (1) reduction of the size of large (≥20 mm) lead vegetations to decrease the likelihood of SPE at the time of CIED removal 13 ; (2) removal of small vegetations in patients with patent foramen ovale 13 ; (3) reduction in the duration of BSI and/ or sepsis in patients who are not "open" surgical candidates such as the case in select PWID cases 16,17 ; and (4) for those who develop severe tricuspid valve regurgitation as a consequence of RSIE, PMA may lead to source control which would facilitate a referral to rehabilitation to treat the underlying addiction in PWID.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding duplicates, 41 case reports and 37 irrelevant studies, 11 studies were included in this targeted literature review. [16][17][18][19][20][21][22][23][24][25][26] Among these, 2 were abstracts and 9 were manuscripts.…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous aspiration of tricuspid valve IE has been reported. 5 , 6 To our knowledge, percutaneous mechanical aspiration of mitral valve vegetation has not been previously reported. Compared with tricuspid valve aspiration, significant challenges exist, including transseptal access and the need for cerebral embolic protection given the risk of systemic embolism.…”
mentioning
confidence: 91%